A protein therapeutic modality founded on molecular regulation - Wright, Chapman M. (National Academy of Sciences, 2011)
The exquisite specificity of proteins is a key feature driving their application to anticancer therapies. The therapeutic potential of another fundamental property of proteins, their ability to be regulated by molecular cues in their environment, is unknown. Here, we describe a synthetic biology strategy for designing protein therapeutics that autonomously activate a therapeutic function in response to a specific cancer marker of choice. We demonstrate this approach by creating a prodrug-activating enzyme that selectively kills human cancer cells that accumulate the marker hypoxia-inducible factor 1α. This property arises primarily through increased cellular accumulation of the enzyme in the presence of the marker. Our strategy offers a platform for the development of inherently selective protein therapeutics for cancer and other diseases.